2006
DOI: 10.1542/peds.2005-0421
|View full text |Cite
|
Sign up to set email alerts
|

Parental Expectations, Physical Punishment, and Violence Among Adolescents Who Score Positive on a Psychosocial Screening Test in Primary Care

Abstract: Perceived parental disapproval of the use of violence may be an important protective factor against youth involvement in violence, and parental use of physical punishment is associated with both violence perpetration and victimization among youth. Parents should be encouraged to clearly communicate to their children how to resolve conflicts without resorting to violence and to model these skills themselves by avoiding the use of physical punishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 29 publications
3
48
0
2
Order By: Relevance
“…Esta conclusão se justifica tendo em vista o constatado por Ohene et al (2006) que verificaram que a percepção de desaprovação parental ao uso da violência relaciona-se a atitudes pró-sociais dos filhos. No caso da presente pesquisa, a opinião percebida nos pais como sendo favorável à ausência de reação e a preponderância de estratégias submissas constatada nos resultados, parece indicar interferência desta natureza.…”
Section: Discussionunclassified
“…Esta conclusão se justifica tendo em vista o constatado por Ohene et al (2006) que verificaram que a percepção de desaprovação parental ao uso da violência relaciona-se a atitudes pró-sociais dos filhos. No caso da presente pesquisa, a opinião percebida nos pais como sendo favorável à ausência de reação e a preponderância de estratégias submissas constatada nos resultados, parece indicar interferência desta natureza.…”
Section: Discussionunclassified
“…Finally, the analysis was limited to, the risk factors included in the GSHS. There are some other potentially important risk and protective factors such as youth and parental attitudes toward fighting (Farrell, Bettencourt, Mays, Kramer, Sullivan & Kliewer, 2012;Ohene, Ireland, McNeely & Borowsky, 2006;Solomon, Bradshaw, Wright & Cheng, 2008) that could be associated with the occurrence of physical fighting that were not measured.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Virtually all adequately designed studies conducted since that meta-analysis have found the same relationship. [19][20][21][22][23][24] In a RCT of an intervention designed to reduce difficult child behaviors, 25) parents in more than 500 families were trained to decrease their use of physical punishment. The significant parallel decline seen in the difficult behaviors of children in the treatment group was largely explained by the parents' reduction of their use of physical punishment.…”
Section: The New Millenium: Addressing Causation and Broadening Focusmentioning
confidence: 99%